2020
DOI: 10.1007/s13311-020-00897-4
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic Dysfunction in Parkinson's Disease

Abstract: Recognition of the importance of nonmotor dysfunction as a component of Parkinson's disease has exploded over the past three decades. Autonomic dysfunction is a frequent and particularly important nonmotor feature because of the broad clinical spectrum it covers. Cardiovascular, gastrointestinal, urinary, sexual, and thermoregulatory abnormalities all can appear in the setting of Parkinson's disease. Cardiovascular dysfunction is characterized most prominently by orthostatic hypotension. Gastrointestinal dysfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 207 publications
0
24
0
Order By: Relevance
“…It can induce degeneration and loss of dopaminergic cells in the substantia nigra compacta, eventually leading to motor symptoms (Ubeda-Bañon et al, 2014). It has been confirmed that LP occurs not only in the central nervous system (CNS), but also in peripheral tissues (Malek et al, 2014), such as the gut (Pfeiffer, 2020). Moreover, the pathological changes of LP in the peripheral nervous system also affect the function of the normal enteric nervous system (ENS), even before the CNS is affected by the pathological changes (Bridi and Hirth, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It can induce degeneration and loss of dopaminergic cells in the substantia nigra compacta, eventually leading to motor symptoms (Ubeda-Bañon et al, 2014). It has been confirmed that LP occurs not only in the central nervous system (CNS), but also in peripheral tissues (Malek et al, 2014), such as the gut (Pfeiffer, 2020). Moreover, the pathological changes of LP in the peripheral nervous system also affect the function of the normal enteric nervous system (ENS), even before the CNS is affected by the pathological changes (Bridi and Hirth, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The loss of dopaminergic neurons in the substantia nigra pars compacta is known to lead to the disinhibition of the micturition reflex in the pons, thus resulting in an overactive bladder in patients with PD ( Jost, 2012 ; Pfeiffer, 2020 ). The role of the diaphragm in reducing urinary incontinence has been demonstrated in a randomized clinical trial which assigned patients with radical prostatectomy to diaphragm training or pelvic floor muscle training, and researchers observed comparable effects between groups ( Zachovajeviene et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with postural instability are more likely to fall, leading to reduced mobility and life expectancy ( Fasano et al, 2017 ). PD involves the accumulation of α-synuclein in multiple visceral systems which play essential roles in the non-motor symptoms ( Pfeiffer, 2020 ), including dysarthria ( Schalling et al, 2017 ), delayed gastric emptying and constipation ( Fasano et al, 2015 ), urinary urgency, and nocturia ( Jia et al, 2020 ). If not treated appropriately, the combination of motor and non-motor symptoms can significantly reduce the quality of life (QoL; Schapira et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Autonomic dysfunction is a common and disabling symptom in PD patients. It increases the risk of falls, exacerbates motor dysfunction, and decreases quality of life [ 30 ]. Among types of autonomic dysfunction, OH affects nearly half of PD patients, representing a major non-motor symptom burden of PD [ 3 , 31 ].…”
Section: Discussionmentioning
confidence: 99%